Developments in the Management of Growth Hormone Deficiency: Clinical Utility of Somapacitan - Miller BS; Blair J; Horikawa R; Linglart A; Yuen KC (Dove Medical Press, 2024)
Bradley S Miller,1 Jo Blair,2 Reiko Horikawa,3 Agnès Linglart,4- 7 Kevin CJ Yuen8 1Division of Pediatric Endocrinology, University of Minnesota Medical School, MHealth Fairview Masonic Children's Hospital, Minneapolis, MN, USA; 2Department of Paediatric Endocrinology, Alder Hey Children's NHS Foundation Trust, Liverpool, UK; 3Division of Endocrinology and Metabolism, National Center for Child Health and Development, Tokyo, Japan; 4Department of Endocrinology and Diabetes for Children, Hospital Bicêtr Paris Saclay, AP-HP, Le Kremlin-Bicêtre, France; 5Unité 1185, INSERM, Paris, France; 6Reference Center for Rare Pituitary Disorders, Hospital Bicêtre Paris Saclay, AP-HP, Le Kremlin-Bicêtre, France; 7Platform of Expertise for Rare Diseases, OSCAR Network, Hospital Bicêtre Paris Saclay, AP-HP, Le Kremlin-Bicêtre, France; 8Departments of Neuroendocrinology and Neurosurgery, Barrow Neurological Institute, University of Arizona College of Medicine and Creighton School of Medicine, Phoenix, AZ, USACorrespondence: Bradley S Miller, Division of Pediatric Endocrinology, University of Minnesota Medical School, MHealth Fairview Masonic Children's Hospital, Riverside Ave, Minneapolis, MN, 55455, USA, Tel +1 612-624-5409, Fax +1 612-626-5262, Email mille685@umn.eduAbstract: Growth hormone (GH) replacement therapy for growth hormone deficiency (GHD) in children and adults has for over 25 years, until recently, been administered as daily injections. This daily treatment regimen often incurs a burden to patients and caregivers, leading to high rates of non-adherence and, consequently, decreased treatment efficacy outcomes. To address this shortcoming, long-acting growth hormones (LAGHs) have been developed with the aim of reducing the burden of daily injections, thereby potentially improving treatment adherence and outcomes. Somapacitan (Sogroya®) (Novo Nordisk, Bagsværd, Denmark) is a LAGH currently approved for the treatment of adult and childhood GHD (AGHD and CGHD, respectively) in several countries. Other LAGHs, such as somatrogon (Ngenla®) (Pfizer, New York, United States) and lonapegsomatropin/TransCon GH (Skytrofa®) (Ascendis Pharma, Copenhagen, Denmark), are also currently approved and available for the treatment of CGHD in several countries. In this review, we will consider the method of protraction, pharmacokinetics (PK) and pharmacodynamics (PD), efficacy, and safety results of somapacitan in adult and pediatric trials and how these characteristics differ from those of the other aforementioned LAGHs. Additionally, the administration of somapacitan and timing of measurement of serum insulin-like growth factor-I (IGF-I) levels are summarized. Information on administration, advice on missed doses, and clinical guidelines are discussed, as well as identifying which patients are suitable for somapacitan therapy, and how to monitor and adjust dosing whilst on therapy.Keywords: (3- 6): growth hormone, long-acting growth hormone, adult growth hormone deficiency, pediatric growth hormone deficiency, adherence